The initiation and development of metamorphic foliation in the Otago Schist, Part 2: evidence from quartz grain-shape data - Stallard, A.; Shelley, D.; Reddy, Steven (Blackwell Science Inc., 2005)
Shape, size and orientation measurements of quartz grains sampled along two transects that cross zones of increasing metamorphic grade in the Otago Schist, New Zealand, reveal the role of quartz in the progressive development of metamorphic foliation. Sedimentary compaction and diagenesis contributed little to the formation of a shape-preferred orientation (SPO) within the analysed samples. Metamorphic foliation was initiated at sub-greenschist facies conditions as part of a composite S1-bedding structure parallel to the axial planes of tight to isoclinal F1 folds. An important component of this foliation is a pronounced quartz SPO that formed dominantly by the effect of dissolution?precipitation creep on detrital grains in association with F1 strain. With increasing grade, the following trends are evident from the SPO data: (i) a progressive increase in the aspect ratio of grains in sections parallel to lineation, and the development of blade-shaped grains; (ii) the early development of a strong shape preferred orientation so that blade lengths define the linear aspect of the foliation (lineation) and the intermediate axes of the blades define a partial girdle about the lineation; (iii) a slight thinning and reduction in volume of grains in the one transect; and (iv) an actual increase in thickness and volume in the survivor grains of the second transect. The highest-grade samples, within the chlorite zone of the greenschist facies, record segregation into quartz- and mica-rich layers. This segregation resulted largely from F2 crenulation and marks a key change in the distribution, deformation and SPO of the quartz grains. The contribution of quartz SPO to defining the foliation lessens as the previously discrete and aligned detrital quartz grains are replaced by aggregates and layers of dynamically recrystallized quartz grains of reduced aspect ratio and reduced alignment. Pressure solution now affects the margins of quartz-rich layers rather than individual grains. In higher-grade samples, therefore, the rock structure is characterized increasingly by segregation layering parallel to a foliation defined predominantly by mica SPO.